Best Answer

The first step is to include an equality sign in it otherwise it is not an equation.

If you mean: 4x = 1-11 then 4x = -10 and x = -10/4

So then: x = -2.5

Q: When solving the equation 4x 1 -11 what is the first step?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5-7m+9m=11

Solving tne simultaneous equation gives x = 19.8 and y = -2.2

x=3 For the equation x + 8 = 11, only one step is required to solve for x Subtract 8 from both sides of the equation to get the x term by itself. 11-8=3, so x=3

If you mean: x = 8y+5 and 3x-2y = 11 then the simultaneous equations can be solved by a process of elimination. -------------------- Since the first equation is solved for x, substitution should be easy. There is no "right" answer to this question - it depends on your taste and experience.

Equations: 7x+4y = 9 and 2x+3y = 1 Multiply all terms in the 1st equation by 2 and all terms in the 2nd equation by 7 So: 14x+8y = 18 and 14x+21y = 7 Subtract the 1st equation from the 2nd equation: 13y = -11 => y = -11/13 By substituting y = -11/13 into any of the equations x = 23/13 Therefore the solutions are: x = 23/13 and y = -11/13

Related questions

5-7m+9m=11

11

How about: x+11 = 33 => x = 33-11 => x = 22

The First Step was created on 1994-11-14.

Start with the equation:x = 11 Then, to make the equation more complicated ("multi-step"), you can do different manipulations, always on both sides of the equation; for example: * Add some number to both sides * Multiply both sides by the same number * Square both sides, or apply some other function to both sides (note: this may introduce additional solutions, depending on the properties of the function applied)

Exosquad - 1993 The First Step 2-11 was released on: USA: 1994

X + 11 = 37. subtract 11 from both sides; X = 37 - 11 = 26.

One-step equation 3x=12 x-6=5 4/x=7 Multistep equation 3x+8=11 x/7+4=6 4x/7=2

Solving tne simultaneous equation gives x = 19.8 and y = -2.2

x=3 For the equation x + 8 = 11, only one step is required to solve for x Subtract 8 from both sides of the equation to get the x term by itself. 11-8=3, so x=3

(\frac{1}{z})^{min(\frac{x-2\sqrt{xy}+y}{2})} = 1

If you mean: x = 8y+5 and 3x-2y = 11 then the simultaneous equations can be solved by a process of elimination. -------------------- Since the first equation is solved for x, substitution should be easy. There is no "right" answer to this question - it depends on your taste and experience.